Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques

Témoin de la nuit: roman - Desai, Kishwar; Dauvergne, Benoîte (L'aube noire, 2013)
Simran Singh est chargée d'une affaire délicate : une adolescente est retrouvée dans la luxueuse maison familiale, bâillonnée et brûlée après avoir été violée. Autour d'elle, treize cadavres empoisonnés. Bientôt, la police soupçonne la jeune fille ! À charge pour Simran de découvrir la vérité, dans une société où naître fille peut s'avérer dangereux…
Keywords: 2000 à aujourd'hui; Roman policier; arts; asie; cours; discipline; inde; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Les monologues voilés - Roosen, Adelheid; Germain, Greg; Drissi, Jamila (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte